Neuroprotective mechanisms of Thai traditional brain tonic Phy-Blica-O against LPS-induced neuroinflammation: Inhibition of NF-κB in microglia and mice - Thammarat Kaewmanee; Palanivel Ganesan; Piyapong Choochana; Pinanong Na-Phatthalung; Samuel Abiodun Kehinde; Sasitorn Chusri (PLoS ONE, 2026)
Phy-Blica-O (PBO) is a traditional Thai polyherbal formulation historically regarded as a brain tonic and memory enhancer. Despite its long-standing ethnomedicinal use, its neuroprotective mechanisms have not been scientifically validated. This study provides the first experimental evidence that PBO alleviates lipopolysaccharide (LPS)-induced neuroinflammation (a process strongly linked to the development of neurodegenerative diseases) through the NF-κB signaling pathway. This study investigates the neuroprotective effects of PBO in lipopolysaccharide (LPS)-induced neuroinflammation, focusing on its ability to modulate the nuclear factor kappa B (NF-κB) signaling pathway in vivo and in vitro . The key constituents of PBO were quantified via high-performance liquid chromatography (HPLC). Antioxidant capacity was evaluated using DPPH, ABTS, and FRAP assays. The anti-neuroinflammatory effects of PBO were assessed in BV-2 microglial cells and male C57BL/6J mice challenged with LPS. Inflammatory mediators and cytokines were quantified at the mRNA and protein levels. NF-κB and MAPK signaling pathway activities were evaluated to elucidate the mechanisms of action of PBO. PBO pretreatment significantly reduced LPS-induced overproduction of nitric oxide (NO) (from 15.69 ± 1.63 to 8.74 ± 0.25 µM at 250 µg/mL, p < 0.001), pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6 mRNA expression reduced by 25%, 31%, and 19%, respectively, p < 0.05), and inflammatory mediators (iNOS and COX-2 protein expression decreased by 41% and 29%, respectively, p < 0.05). Mechanistic analysis revealed that PBO exerts its protective effects primarily through inhibition of the NF-κB signaling pathway, reducing p-IκBα levels by 23% (p = 0.018) and p-p65 levels by 34% (p = 0.039) at 250 µg/mL in vitro, with no significant effect on MAPK signaling. These in vitro findings were corroborated by in vivo outcomes, where oral PBO administration (100 mg/kg for 7 days) significantly lowered iNOS and COX-2 mRNA expression (p = 0.041 and p = 0.018, respectively) and pro-inflammatory cytokine levels in the brains of LPS-challenged mice. Collectively, the results substantiate the traditional use of PBO as a neuroprotective tonic and highlight its potential as a cost-effective therapeutic candidate for preventing or managing neuroinflammatory conditions associated with neurodegeneration. Further studies are warranted to assess its bioavailability, long-term safety, and behavioral efficacy.